(untitled) (Italian Journal of Public Health, 2012)
Personalised healthcare can be defined as a customisation of the medical provision that accommodates individual differences in all stages in the process, from prevention, to diagnosis and treatment, to post-treatment follow-up. While the term personalized medicine...